Old Sarum: Archaeological Interventions in the West Suburbs, 2017-2019 - Alexander Langlands (2023)
Evaluation undertaken in 2017-2019 identified the original canon's closes, a probable flood plain settlement of Saxo-Norman or earlier date and 13th to 14th century house platforms. The ground plan for the historically attested canons' houses and gardens of the late 11th century were identified. The closes are defined as a series of plots laid out in regular fashion perpendicular to Philips Lane and extending across it into a narrow roadside terrace. The recovery of 13th century pottery sealed within the bank of the Croft adjoining the Bean Closes indicates the bank is not related to the setting out of the canons' residences but is part of a later re-organisation of the area. Likewise, to the north of Phillips Lane, the field boundary of Phillip's Upper Croft would appear to overlie the canons' closes and appears to have been set out at a later date. By the middle of the 16th century, the suburb on the west of Old Sarum was no longer in existence; the sudden move of the cathedral in the early 13th century would almost certainly have played a role in its abandonment. Only four sherds of 15th to 16th century pottery were recovered suggesting activity tailed off quickly. The recovery of 10th century pottery from the alluvial plain supports the identification of a riverside settlement of this period with a focus lying somewhere beneath Deans Farm and the Manor House to the north. The preponderance of 13th century pottery from the assemblage here suggests that this settlement went on to be co-existent with the occupation of the canons' residences. Activity on the riverside gravel terrace in the 13th century is indicated by two house platforms. Fragments of masonry which may have been robbed from the cathedral site were recorded suggesting a date of occupation for these buildings contemporaneous with the demolition of the cathedral. The pottery recovered from the platform banks also support this and suggest the buildings were relatively short-lived. Evaluation undertaken in 2017-2019 identified the original canon's closes, a probable flood plain settlement of Saxo-Norman or earlier date and 13th to 14th century house platforms. The ground plan for the historically attested canons' houses and gardens of the late 11th century were identified. The closes are defined as a series of plots laid out in regular fashion perpendicular to Philips Lane and extending across it into a narrow roadside terrace. The recovery of 13th century pottery sealed within the bank of the Croft adjoining the Bean Closes indicates the bank is not related to the setting out of the canons' residences but is part of a later re-organisation of the area. Likewise, to the north of Phillips Lane, the field boundary of Phillip's Upper Croft would appear to overlie the canons' closes and appears to have been set out at a later date. By the middle of the 16th century, the suburb on the west of Old Sarum was no longer in existence; the sudden move of the cathedral in the early 13th century would almost certainly have played a role in its abandonment. Only four sherds of 15th to 16th century pottery were recovered suggesting activity tailed off quickly. The recovery of 10th century pottery from the alluvial plain supports the identification of a riverside settlement of this period with a focus lying somewhere beneath Deans Farm and the Manor House to the north. The preponderance of 13th century pottery from the assemblage here suggests that this settlement went on to be co-existent with the occupation of the canons' residences. Activity on the riverside gravel terrace in the 13th century is indicated by two house platforms. Fragments of masonry which may have been robbed from the cathedral site were recorded suggesting a date of occupation for these buildings contemporaneous with the demolition of the cathedral. The pottery recovered from the platform banks also support this and suggest the buildings were relatively short-lived.